Keratoconus associated with Fuchs’ Corneal Endothelial Dystrophy in a Young Woman: A Case Report - Bajracharya, Leena; Getachew, Rebecca; Seng, Serey (Nepalese Journal of Ophthalmology, 2024)
Introduction: Keratoconus has association with various ocular diseases. Here a case of the co-occurrence of keratoconus and Fuchs’ corneal endothelial dystrophy (FCED), a rare entity has been reported. Case: A 26-year-old woman presented with a sudden onset of blurring of vision of right eye (RE) three weeks back. Observation: The RE showed features of advanced keratoconus with apical scaring due to acute hydrops. Her left eye (LE) had myopic astigmatism with Vogt's striae. Careful examination revealed corneal guttate in both eyes. The co-existence of keratoconus and FCED was confirmed by tomographic scans and specular microscopy. The patient underwent penetrating keratoplasty in RE. The LE was planned for cross-linking therapy if keratoconus would progress. Conclusion: Keratoconus and FCED have opposing effects on corneal thickness, resulting in reciprocal masking of the severity and progression of either condition. Corneal scans must be interpreted with caution as keratoconus and FCED differ completely in terms of their treatment options.